Analisis Penerimaan Terhadap Penerapan Sistem E-Learning Menggunakan Technology Acceptance Model (TAM) - Tuska Abe; Anton Yudhana; Imam Riadi (STMIK Budi Darma, 2020)
E-laerning is an electronic media that functions as a tool to facilitate students in absorbing and obtaining material. The e-learning system itself has been implemented in Talam West Huamual High School as a learning aid, but the application of the e-learning system students need to familiarize themselves with the learning system that has just been studied by previous learning media. the purpose for assessing the level of students of the level of acceptance of e-learning systems in schools. This study involved 35 students as respondents in the West Huamual Talaga High School. The model uses the technology acceptance model (TAM). The data analyzed in this study used descriptive analysis according to category and percentage. Based on the results of the study that showed e-learning system of West Talaga huamual high school for user-suitable analysis according to the category of